Footnotes, artistic conception, and strategies in translation of ancient Chinese poetry into English - Hee, May Yee; Wong, Xin Yi; Yuan, Jiang; Amini, Mansour (AJELP: Asian Journal of English Language and Pedagogy, 2022)
In Chinese poetry, artistic conceptions (Yi Jing), i.e., the soul of poetry portrayed beyond the words, has often underrated. This research explored the translatability of Chinese poetry from the perspective of maintaining artistic concepts by applying Vinay and Darbelnet ‘s model, exploration of the strategies, and footnotes. Five ancient poems that contained significant Chinese culture specific items were selected. The strategies utilized in the translation of the ancient poetries from Chinese to English language were identified and described, in addition to the thematic analysis used to analyze the content of footnotes and how artistic conception was preserved in the poem translations. Findings showed that “equivalence” is the most used strategy in the translation of the five poems, followed by “modulation”, “literal translation”, “transliteration”, “borrowing and adaptation”. Moreover, the difficulty of poetry translation from Chinese to English was identified to be mostly related to the elements that reflected on the cultural and historical background. It was concluded that adding footnotes can help to preserve the artistic conceptions and intentions of the source text without causing confusion among readers in translating ancient Chinese poems. The findings could provide insights on the translatability of poetry and how footnotes help in maintaining artistic conception and the intended meaning, emphasising on appropriate strategies for preserving the artistic conception.